Computational Facilities and Web-Resources: Case Study of Large Private University with Fast-Growing Clients - Das, Srikanta Charana; Subudhi, Rabi N.; Patra, Arun Kumar (Journal of Reviews on Global Economics, 2018)
Speed, space and judicious sharing web-related resources are the key indicators of successful management of the computing-facilities and other web-resources of any progressive organisation. Such a case becomes much more demanding for any professional academic institution, where the majority stake-holders, that is the young student-users of web-resources, are heavily dependent on web-based learning and personal communications. Other stake holders, like administrative staff, teaching and research community of universities have web-dependence, mostly for known resources. Fast growing dependence of different categories of stake-holders of such large institutes warrants a case-study research, so as to study the present pattern of uses of web-resources, including the timing and pockets of users, and then to have a sustainable strategic planning for a better resource-management of web-resources for future. The present paper is a case study of a leading private university of Odisha (in India) with over 65,000 users of â€˜university web-network’ and over 7500 fixed-systems, which analyses users’ time-series data of last quarter and suggests a futuristic model for optimal and effective use of - ˜Institute Web-Resources and computing facilities’. It studies both fixed-line load and load-management of wireless (Wi Fi) connections, across the 25 campuses of the Institute, scattered and geographically located within 15 sq. km.